Effect of rice quality, formulation and storage on the quality of canned rice porridge - Ma, Yong Qin (2000)
Long-grain rice was mixed with broken rice or glutinous rice at a ratio of 0:100, 25:75, 50:50, 75:25 and 100:0, respectively. Each mixture was processed into canned plain rice porridge. The physical and sensory properties of the products were evaluated. An optimum ratio was selected for the preparation of savoury rice porridge (chicken, beef, fish and bean flavours). The freshly prepared savoury rice porridges were then evaluated to determine their physicochemical, microbiological and sensory qualities. A storage study was also carried out to determine the quality changes of canned savoury rice porridges stored at 27°C and 4°C for 12 weeks. The results obtained showed that plain rice porridge was best prepared using 100% long-grain rice. However, plain rice porridge prepared using a mixture of broken rice and long-grain rice at a ratio of 50:50 was found to be as acceptable as that containing 100% long-grain rice. Incorporation of glutinous rice reduced phase separation but in excess of 25 percent led to a significant decrease in acceptability. Physical characteristics of the plain rice porridge were relatively unchanged with the substitution of long-grain rice with broken rice. When long-grain rice was substituted with increasing amounts of glutinous rice, the pH value and whiteness of the plain rice porridge tended to decrease but its %Brix and viscosity increased gradually. For the savoury rice porridges, the results of the ranking test revealed that the fish rice porridge was the most preferred followed by the beef, chicken and bean rice porridges in terms of colour, texture, flavour and taste. Results of the nutrient composition analyses showed that the beef rice porridge provided the highest protein, fat, and caloric contents and the most amounts of calcium and iron. Results of the storage study indicated that the temperature and time of storage did not affect dry matter, ash, protein, fat, caloric, calcium and iron content of the porridges. However, low storage temperature caused the porridges to have a lower %Brix and increase in whiteness. Porridges stored at room temperature were more stable in appearance, colour, flavour and taste than those stored in the refrigerator. A composite of broken rice and long-grain rice at a ratio of 50:50 is recommended for the production of plain rice porridge. A can of the four types of savoury rice porridges designed can provide 1/4- 1/5 of the recommended daily allowance (RDA) for energy and nutrients for 7-12 years old children. All samples stored at room temperature or in the refrigerator complied with the standard for food hygiene and safety up to 12 weeks of storage. However, canned rice porridge stored at room temperature gave better sensory characteristics.